Vitrolife private equity investment committee paper - business plan - Berg, Laura (2023)
The target company, Vitrolife provides Medical Consumables, Technological Devices (C&T) and Genetic Testing services (GT) for in-vitro fertilization. C&T has a market size of SEK 15bn (CAGR of 14.3%) while GT’s market size is SEK 41bn (CAGR of 6.7%). Value creation is driven through an AI software partnership, the Eastern Europe Penetration and the acquisition of Virtus Health. Most of the value is driven by inorganic growth (50%). Based on a 16.7x exit multiple and an Enterprise Value of SEK 17,250m, a MM of 3.6x can be realized over the holding period. Sources of funds include SEK 5,693m (5.5x) debt and SEK 12,418m (12x) equity.